Blue Ocean strategy for the port sector (synchromodality and digitization) (2020)
Industry in general and ports in particular are moving towards 4.0 processes. The use of new technologies and new market patterns are the main tools for the success of these processes. The current challenges of the port sector are to develop Smart ports whose main characteristics are defined by digitalization and synchro-modality. Only they allow determining a new scenario in which it is possible to raise the Blue Ocean Strategy, leaving aside competition and looking for a new demand. The growing development of digital techniques and their implementation in port management and transport processes makes this strategy viable on an even greater scale. The general conclusion of the research is that it is possible to apply market strategies to the Spanish port sector with a different methodology to the one used until now. It can be seen that Spanish ports, still have a long way to go in terms of sustainability, understood in three dimensions: economic, social and environmental.